Regional security dialogue in the Middle East : changes, challenges and opportunities - Kane, Chen; Murauskaite, Egle (London ; New York, NY : Routledge, 2014)
"At this time of considerable political turmoil in the Middle East, with little progress observable in the Arab-Israeli peace process and Iran's continuing pursuit of a nuclear program, there is a pressing need to explore alternative frameworks for regional security. The book discusses the Helsinki Process as one potentially relevant historical model to learn from. The Helsinki Process began in a divided Europe in the early 1970s and, over 40 years, achieved major successes in promoting cooperation between the Warsaw Pact and NATO member states on social, human rights, security, and political issues. In this volume, established Middle East experts, former diplomats, and emerging scholars assess the regional realities from a broad range of perspectives and, with the current momentum for reform across the Middle East, chart a path towards a comprehensive mechanism that could promote long-term regional security. Providing a gamut of views on regional threat perception and suggesting ways forward for regional peace, this book is essential reading for students and scholars with an interest in Politics, the Middle East and Conflict Studies"--
Cautious optimism : the Helsinki process as a model for negotiations in the Middle East / Ambassador Lynn M. Hansen -- A zone in the Middle East : confidence building measures, the European experience / Ambassador Rolf Ekéus -- The Helsinki process and the Middle East : the viability of cooperative security frameworks for a region in flux / Ambassador Nabil Fahmy and Karim Haggag -- The Helsinki process and its relevance in a changing Middle-East : an Israeli perspective / Dr. Ehud Eiran -- Nuclear-weapon-free zone in the Middle East : a political view / HRH Prince Turki Al Faisal of Saudi Arabia and Dr. Awadh Al-Bad -- Domestic politics in Iran and a future regional process / Ariane M. Tabatabai -- Lessons learned : the Turkish role in arms control and regional security talks in the Middle East / Nilsu Goren -- The Helsinki process in the Middle East : promoting security, development, democracy and peace / Dr. Gershon Baskin and Hanna Siniora -- The future of arms control in the Middle East / Bilal Saab -- The Middle East and the Helsinki process : unfulfilled aspiration, so far / Dr. Mike Yaffe -- Civil society dialogues and Middle East regional security / Dr. Peter Jones -- A Helsinki process for the Middle East? : new discourse, new opportunities / Dr. Patricia Lewis and Karim Kamel -- Conclusion : charting a course inspired by the Helsinki experience / Dr. Chen Kane.
Includes bibliographical references and index.
Keywords: Helsinki Process on Globalisation and Democracy; Security, International -- Middle East; Strategic culture -- Middle East; Arms control -- Middle East; Middle East -- Foreign relations; POLITICAL SCIENCE / International Relations / Diplomacy; SOCIAL SCIENCE / Regional Studies